The undergraduate economics coursework of elementary and secondary school teachers. Issue 4 (2nd October 2019) - Bosshardt, William B.; Walstad, William
Abstract: In this study, the authors analyze the undergraduate economics coursework of U.S. college graduates who became pre-college classroom teachers. The results show that teachers successfully completed on average the equivalent of about half an economics course in their undergraduate coursework. About 6 in 10 teachers earned no course credits in economics. Of teachers certified to teach social studies—the ones most likely to teach economics—40 percent did not take an undergraduate course in economics. The percentages are 19 percent for high school teachers, 48 percent for middle school teachers, and 76 percent for elementary school teachers. High school teachers certified to teach social studies completed an average of only about one and a half economics courses as undergraduates.